Poetic Cartography, Love, and Loss: On Piecing Together a Father - Francesca Rendle-Short (NANO, 2014)
In setting out to write my father in the making of the experimental artefact that accompanies this essay, a poetic cartography in a series of photographs I am calling “A Matter of View: (From a Set of Annotations),” I risk disinheritance. The six found photographs and accompanying postcard text chart the last days of my father’s life and my correlation to this event before he died in his nursing home on the Great Dividing Range in southeast Queensland, Australia. It is a precarious loop into and out of the body that I am making, return and departure, to evoke Borich’s description, but cartography I am intent on composing despite any perceived or hidden danger. Is it worth the gamble?